Three-dimensional spreading of prestressing forces in box girders. (October 2021) - He, Zhi-Qi; Hong, Hao; Liu, Zhao; John Ma, Zhongguo
Abstract: In most applications of post-tensioning, especially for bridge girders, the cross section over which the post-tensioning acts is not rectangular. Since the design of the box girder anchorage zone is not currently addressed in any code provisions, a detailed investigation of the three-dimensional (3D) spreading of the tendon force in flanged sections is required. To accomplish this objective, a computer-based tool is developed for plotting load paths in 3D bodies, from which the flow of forces in the box-girder anchorage zone can be clearly visualized. It is found that the 33.7-degree criterion is appropriate to describe the dispersion of the tendon force in the box-girder. Meanwhile, planar strut-and-tie models are built to approximate the flow of forces in orthogonal planes of the box section. As a useful supplement to the current design codes, direct equations are established for the design of the box-girder anchorage zone. Finally, a case study is carried out to find the cause of cracking in a span-by-span constructed box-girder bridge. The large transverse tensile stress in the bottom flange is primarily caused by the post-tensioning of web tendons, indicating the importance of 3D effects in the box-girder anchorage zone.